2008
DOI: 10.1161/circresaha.108.181644
|View full text |Cite
|
Sign up to set email alerts
|

P53 Impairs Endothelium-Dependent Vasomotor Function Through Transcriptional Upregulation of P66shc

Abstract: Abstract-The transcription factor, p53, and the adaptor protein, p66shc, both play essential roles in promoting oxidative stress in the vascular system. However, the relationship between the two in the context of endothelium-dependent vascular tone is unknown. Here, we report a novel, evolutionarily conserved, p53-mediated transcriptional mechanism that regulates p66shc expression and identify p53 as an important determinant of endothelium-dependent vasomotor function. We provide evidence of a p53 response ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 24 publications
2
69
0
Order By: Relevance
“…Moreover, pancreatic islets isolated from HFD-fed mice displayed robust increases in p66 Shc mRNA expression, establishing a link between in vivo lipotoxicity and p66 Shc regulation. Both the use of pifithrin-α, an inhibitor of p53 function, and siRNA-mediated p53 knockdown allowed us to prove that the ability of saturated FAs to promote p66 Shc expression is mediated by p53, in line with similar results in other cell systems [23]. We found that p53 expression was increased in response to palmitate in both mouse islets and INS-1E beta cells, as well as in human islets from overweight/obese compared with normal-weight donors.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Moreover, pancreatic islets isolated from HFD-fed mice displayed robust increases in p66 Shc mRNA expression, establishing a link between in vivo lipotoxicity and p66 Shc regulation. Both the use of pifithrin-α, an inhibitor of p53 function, and siRNA-mediated p53 knockdown allowed us to prove that the ability of saturated FAs to promote p66 Shc expression is mediated by p53, in line with similar results in other cell systems [23]. We found that p53 expression was increased in response to palmitate in both mouse islets and INS-1E beta cells, as well as in human islets from overweight/obese compared with normal-weight donors.…”
Section: Discussionsupporting
confidence: 69%
“…Prolonged exposure of beta cells to elevated palmitate concentrations has been shown to cause downstream JNK activation and increased p53 expression, events which are in part mediated by enhanced oxidative stress and typically linked to cellular damage [7, 24, 33, this study]. The identification of a p53 response/binding element in the promoter region of p66 Shc indicated that p66 Shc is a p53 target gene and that p66 Shc is indispensable for p53-induced apoptosis [22,23,34]. In this study, murine and human islets, as well as INS-1E cells, showed increased levels of p66 Shc when chronically exposed to elevated palmitate concentrations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The HG has been shown to increase the synthesis of ANG II (8) and expression of p53, a transcription factor. Interestingly, the consensus sequences for the binding of this transcription factor have been localized in the promoter region of p66Shc (19). Thus the observed increase of p66Shc mRNA expression in DN may be via the ANG II-induced modulation of p53.…”
Section: Discussionmentioning
confidence: 98%
“…NRK52E cells were transfected with the following reporter luciferase plasmids: p66shc promoter (14), antioxidant response element (ARE; Qiagen, Germantown, MD, USA) and a HO-1-promoter (15) together with a Renilla luciferase (Promega, Madison, WI, USA) using Lipofectamine 3000 reagent (Life Technologies, Grand Island, NY, USA) as recommended by the manufacturer. 24 h after treatment firefly and renilla luciferase activities were determined using the Dual Luciferase assay kit (Promega, Madison, WI, USA) as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%